Regulation or deregulation of the accounting profession in a sustainable economy? Evidence from Poland - Stanisław Hońko; Marzena Strojek-Filus; Katarzyna Świetla (International Entrepreneurship Review, 2023)
Objective: The article aims to examine how accountants assess the effects of deregulation in the accounting profession in Poland. Our study also included accountants’ expectations regarding the regulation of the accounting profession in the future.